Challenges of Quantifying Meltwater Retention in Snow and Firn: An Expert Elicitation - van As, Dirk; Box, Jason E.; Fausto, Robert S. (Frontiers in Earth Science, 2016)
Thirty-four experts took part in a survey of the most important and challenging topics in the field of meltwater retention in snow and firn, to reveal those topics that present the largest potential for scientific advancement. The most important and challenging topic to the expert panel is spatial heterogeneity of percolation, both in measurement and model studies. Studying percolation blocking by ice layering, particularly in modeling, also provides large potential for science advancement, as well as hydraulic conductivity and capillary forces in snow/firn. Model studies can benefit from improved initialization, and improved calculation of accumulation and liquid water at the surface. Firn coring should be performed more often, though we argue that also data that are relatively simple to collect, but of great importance to retention such as surface accumulation, density and temperature, are too sparse due to the high logistical expenses involved in field campaigns. Generally speaking, retention changes are expected to be of importance to the climatic (surface) mass balance and thus ice loss in coming decades, more so for Greenland than Antarctica or ice masses elsewhere.